2018
DOI: 10.1007/978-3-319-99519-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Printable Concrete Thixotropy by High Shear Mixing

Abstract: Our results show that the storage elastic modulus as a function of time increases at a higher rate for the cement paste mixed at higher versus lower mixing intensity. Hence, higher mixing appears to be enhancing thixotropy. Using calorimetry analysis we find that higher mixing decreases the setting time and enhances the peak of the heat flow. By analyzing the nanoparticles present in the suspending fluid of the cement paste, we show, in accordance with literature, that an appropriate combination of mixing ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has, for example, been shown that the mechanical properties of cementitious materials depend on the energy of mixing [6,7]. Moreover, high-shear mixing can induce the crushing of solid particles, which can lead to enhanced structural build-up rates in the fresh state, thus proving useful in ensuring global stability of the printed system at early ages [8]. However, a high level of process control is required to enable this.…”
Section: Mixingmentioning
confidence: 99%
“…It has, for example, been shown that the mechanical properties of cementitious materials depend on the energy of mixing [6,7]. Moreover, high-shear mixing can induce the crushing of solid particles, which can lead to enhanced structural build-up rates in the fresh state, thus proving useful in ensuring global stability of the printed system at early ages [8]. However, a high level of process control is required to enable this.…”
Section: Mixingmentioning
confidence: 99%